1992
DOI: 10.3171/jns.1992.77.3.0355
|View full text |Cite
|
Sign up to set email alerts
|

Adult intramedullary astrocytomas of the spinal cord

Abstract: In this series, 25 adult patients with intramedullary astrocytomas were treated by radical excision alone. Six patients proved to have anaplastic astrocytoma; five of them died within approximately 2 years and the sixth has demonstrated disease progression. The other 19 patients were diagnosed as having low-grade astrocytoma (16 cases) or ganglioglioma (three cases); two of these had advanced preoperative neurological disability and died of medical complications. Fifteen of the remaining 17 patients have no cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(105 citation statements)
references
References 16 publications
5
97
0
3
Order By: Relevance
“…1,2,10 Reports regarding the selection of the surgical procedure varied from those encouraging aggressive resection 11,12 to those claiming that a biopsy may result in a better functional outcome; 1,2,10,13 and this issue remains controversial. During the past 10 years, we have attempted vigorously to totally remove astrocytomas whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,10 Reports regarding the selection of the surgical procedure varied from those encouraging aggressive resection 11,12 to those claiming that a biopsy may result in a better functional outcome; 1,2,10,13 and this issue remains controversial. During the past 10 years, we have attempted vigorously to totally remove astrocytomas whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Also, one category B study reported significantly better 10-year OS in patients receiving GTR or PR when compared to biopsy only [51]. In addition, in the study of Epstein (category A), where all 17 patients received GTR, no recurrence was observed during a mean follow-up of 50 months [15].…”
Section: Syrinx/cyst Presencementioning
confidence: 98%
“…Results for EOR specifically for HG histology were reported in nine studies, four were classified as category A [5,15,34,46], five as category B [11,27,51,52,65] (Table 13, lower part). Only one category A study reported increased 4-year OS in anaplastic astrocytoma (grade III) patients [46]; those receiving GTR had significantly improved survival (78% at 5 years) when compared to patients with STR (38% at 5 years, p = 0.028).…”
Section: Syrinx/cyst Presencementioning
confidence: 99%
“…[1][2][3] Because of the rarity of this tumor, optimal treatment guidelines have yet to be defined. The traditional treatment strategy for intramedullary astrocytoma is a biopsy to confirm the diagnosis followed by radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, the efficacy of this treatment has been a subject of controversy. Important but presently unsettled issues include the impact of the extent of resection on local control and survival 1,5,6 and the significance of postoperative radiation therapy. 7 The purpose of the present study was to obtain useful information to establish decision-making guidelines for the treatment of spinal cord astrocytoma by examining the clinical records of patients treated at Keio University Hospital.…”
Section: Introductionmentioning
confidence: 99%